Development and validation of nomograms to forecast overall survival and cancer-specific survival in Asian patients diagnosed with epithelial ovarian cancer - Hao He; Xin Cheng; Mengna Zhao; Shimeng Wan; Shijie Yao; Hongbing Cai (Frontiers in Surgery)
ObjectiveAsian females with ovarian cancer have different clinicopathological characteristics compared with other races. However, an effective prognostic prediction tool is lacking. The goal of our study was to develop and evaluate nomograms for estimating overall survival and cancer-specific survival in Asian patients with ovarian cancer.MethodsWe extracted data from 2010 to 2018 in the Surveillance, Epidemiology, and End Results database, focusing on Asian/Pacific Islander females that had been diagnosed with epithelial ovarian cancer. To find prognostic factors, least absolute shrinkage and selection operator Cox regression and multivariate Cox regression analyses were used. Based on the outcomes, nomograms were then constructed. Numerous techniques, such as the C-index, calibration plots, decision curve analysis, and risk subgroup stratification, were used to assess the performance of the nomograms.ResultsNomograms were created to evaluate overall survival and cancer-specific survival rates over three and five years. The C-indices for overall survival and cancer-specific survival in the training cohort were 0.768 and 0.778, respectively. The C-indices for overall survival and cancer-specific survival in the validation cohort were 0.804 and 0.812, respectively. The calibration plots showed that the nomogram forecasts and actual survival results agreed. Additionally, the decision curve analysis curves indicated that the nomogram outperformed the American Joint Commission on Cancer staging system in terms of predictive accuracy.ConclusionNomograms and a risk classification system were created to forecast the overall survival and cancer-specific survival of Asian females with ovarian cancer. The nomograms and risk stratification system have the potential to provide valuable assistance in making future clinical decisions.